Overcoming difficult, impossible, and meaningless animal testing under REACH: Opportunities for robust chemical risk assessment with non-animal approaches - Martijn van Velthoven; Giorgia Pallocca; Vicente Aranda; Anders Bergqvist; Maria Blanco-Rubio; Kevin Bonnot; Jay Dawick; Mojca Fuart-Gatnik; Marlly Guarin; Steve Gutsell; Jean Knight; Aleksandra Mostrag-Szlichtyng; et al. (Regulatory Toxicology and Pharmacology, 2026)

Potent cytotoxicity of plumbagin targets human glioblastoma and colorectal carcinoma - Valquíria de Faria Neves; Benito Soto-Blanco; Luciana Maria Silva; Maiara Fonseca Cupertino de Oliveira; Silvia Catarina Salgado Oloris (Toxicon, 2026)

First record of Prorocentrum caipirignum in Rapa Nui (Easter Island) and its production of okadaic acid: Implications for DSP risk in the southeastern Pacific - Gonzalo Álvarez; Juan Blanco; Maria García-Portela; Francisco Rodríguez; Valentina Hevia-Hormazabal; Michael Araya; Moiko Pakomio; Valentina Silva; Rosario Díaz; Pamela Averill; Emilia Palma Tuki; Carlos Gaymer; et al. (Harmful Algae, 2026)

Extreme Saharan dust outbreak: Air quality crisis in NW Spain (March 2022) - Cátia Gonçalves; Estela D. Vicente; Carlos Blanco-Alegre; Ana Isabel Calvo; Maria del Mar Sorribas; Fabio Giardi; Silvia Nava; Giulia Calzolai; Alberto Rodríguez-Fernández; Carla Candeias; Roberto Fraile (Atmospheric Pollution Research, 2026)

Circulating metabolites and fatty acids associated with ultra-processed food consumption: results from the EPIC study - Jessica Blanco-Lopez; Sahar Yammine; Joseph A. Rothwell; Mathilde His; Carine Biessy; Pekka Keski-Rahkonen; Bernadette Chimera; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; Oliver Robinson; Fernanda Morales Berstein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Application of FT-IR spectroscopy using the IR Biotyper® for Leptospira: protocol optimization and first spectral insights - Amanda Maria Jesus Bertani; Elaine Santos Lima; Natalia da Cunha Nobrega; Marcelo Sansone; Juliana Alves Garcia; Daniela Leite; Gisele Oliveira de Souza; Tamires Santos de Arruda; Ricardo Polatto; Eliete Calo Romero; Tania Sueli de Andrade; Karoline Rodrigues Campos; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Superovulation with eCG alone or combined with the GnRH analogue buserelin improves transferable embryo production in weaned sows without affecting Day 6 embryo morphological, cellular, and transcriptomic parameters - Adelina Lopez-Jara; Manuela Garcia-Canovas; Henar Gonzalez-Ramiro; Carolina G. Cabrera-Gomez; David Gascon-Collado; Paula Blanco-Cueto; Maria A. Gil; Cristina Cuello; Inmaculada Parrilla; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano (Animal Reproduction Science, 2026)

Microplastic characterization and abundance in stomach contents of the American crocodile (Crocodylus acutus) from Cozumel, Mexico - Diana Marcela Caro-Martínez; Carlos Alberto Niño-Torres; Jaime Rendón-von Osten; Delma Nataly Castelblanco-Martínez; Lorena M. Rios-Mendoza; Oscar Frausto-Martínez; Maria del Pilar Blanco-Parra; Merle Marisa Borges-Ramírez; Pierre Charruau (Regional Studies in Marine Science, 2026)

Community-Based Mangrove Management in Sucre, Colombia: Stakeholder Perceptions, Land Cover Trends, and Challenges - Ángela M. Barrera-Bello; Alexandra Rodríguez-Rodríguez; Ana Maria Valencia Palacios; Jaime Polanía; Jose M. Riascos; Juan Felipe Blanco-Libreros; Jean Hugé; Farid Dahdouh-Guebas (Ethnobotany and Economic Botany, 2026)

Postnatal particulate matter exposure alters developmental milestones and brain gene expression in apoE transgenic mice in a sex- and genotype-dependent manner - Rocío Rodulfo-Cárdenas; Judit Biosca-Brull; Séfora Barberà-Parada; Raquel Gabaldón-Díaz; Diego Ruiz-Sobremazas; Jordi Blanco; Maria Cabré; José L. Domingo; Caridad López-Granero; Fernando Sanchez-Santed; Maria Teresa Colomina (NeuroToxicology, 2026)

Rural women's voices and gender dynamics in colombian land restitution policy: A case study review in valle del cauca, Colombia - Maria Blanco; Fanny Howland; Alexander Buritica; Carolina Gonzalez (Journal of Rural Studies, 2026)

Transverse structure of tidal and exchange flows in a Magellan glacial fjord - Maria Fernanda Gastelu-Barcena; Arnoldo Valle-Levinson; José Luis Blanco (Journal of Marine Systems, 2026)

Sustainable rare earth capture using seashell carbonates: Mineralogical pathways and comparative uptake behaviour of mussel, cockle, and oyster shells - Rémi Rateau; Melanie Maddin; Adrienn Maria Szucs; Luca Terribili; Paul Christopher Guyett; Kristina Petra Zubovic; Juan Diego Rodriguez-Blanco (Science of The Total Environment, 2026)

Identification of common types of plastics by vibrational spectroscopic techniques - Maria P.Garcia Tovar; Maria A.Villarreal Blanco; Oliva M. Primera-Pedrozo; Macy K. Christianson; Chih-Feng Wang; Pavel Valencia Acuña; John H. Miller; Luis de la Torre; Samuel P.Hernández Rivera (Resources, Conservation and Recycling, 2026)

Synergistic dual-pathway activation of peroxymonosulfate via topochemically engineered A-site deficient BaMnO3 perovskite for advanced water decontamination - Yu Shen; Verónica Blanco-Gutiérrez; Giulio Gorni; Maria J. Sampaio; Adrián M.T. Silva; Ana R. Lado Ribeiro; Jingqing Gao; Antonio J. Dos santos-García (Journal of Hazardous Materials, 2026)

Design and scale-up of a hydrogen oxy-fuel burner for high-temperature industrial processes - Pablo Barreiro; Isabel Alava; Jesus Maria Blanco (Fuel, 2026)

Developing narratives for policy-relevant water-energy-food-ecosystem nexus pathways: How global and European Union drivers interact - Imen Arfa; Adrián González-Rosell; Kristina Govorukha; Berny Bisselink; Maria Blanco (Environmental Impact Assessment Review, 2026)

Multimodal deep learning for cyanobacteria classification: a fusion of CNN and transformer architectures - Maria Blanco; Jesús Ruiz-Santaquiteria; Gabriel Cristóbal; Elvira Perona; Gloria Bueno (Aquatic Ecology, 2025)
Cyanobacteria play a fundamental role in aquatic ecosystems, contributing to global biogeochemical cycles and serving as indicators of environmental change. Their classification is critical for monitoring water quality, detecting harmful algal blooms and understanding ecosystem dynamics. However, accurate identification remains a major challenge due to their vast taxonomic diversity and significant morphological similarities. Visual inspection alone is often insufficient, highlighting the need for computational approaches to enhance classification accuracy. In this study, we present a multimodal deep learning model that combines convolutional neural networks (CNNs) for image-based feature extraction with bidirectional transformers for text embedding. These complementary features are fused via concatenation to improve species-level classification. To our knowledge, this is the first application of a multimodal neural architecture integrating CNNs and bidirectional transformers for cyanobacteria classification. We evaluated five CNN backbones of varying depth, resulting in eight model configurations. Performance is benchmarked against unimodal CNN models that rely solely on image data. The model is trained and validated on a dataset of 1660 microscopic images and corresponding textual descriptions, covering nine cyanobacterial genera across three taxonomic orders. Results demonstrate the potential of multimodal deep learning to improve classification performance, supporting the development of scalable and accurate identification tools in microbiology and environmental monitoring.

A Water-Energy-Food-Ecosystems nexus coherence assessment of solutions in the Danube River Basin - Adrián González-Rosell; Beáta Pataki; János Fehér; Imen Arfa; Attila Lovas; Maria Blanco (Science of The Total Environment, 2025)

Petrographic characterization of organic matter and solid bitumen from the Pimenteiras Formation (Devonian), Parnaíba Basin (Brazil), potential for hydrocarbon generation - Agostinho Mussa; Wolfgang Kalkreuth; Ana Maria Pimentel Mizusaki; Marleny Blanco González; Tais Freitas da Silva (Ore and Energy Resource Geology, 2025)

Impact of a high-fat diet on spatial learning and memory: The role of sex, APOE genotype, and postnatal chlorpyrifos exposure - Laia Guardia-Escote; Judit Biosca-Brull; Jordi Blanco; Maria Cabré; Pia Basaure; Cristian Pérez-Fernández; Fernando Sánchez-Santed; José L. Domingo; Maria Teresa Colomina (NeuroToxicology, 2025)

The state of microplastic pollution in México: a review and evolving perspectives - Diana Marcela Caro-Martínez; Carlos Alberto Niño-Torres; Pierre Charruau; Jaime Rendón-von Osten; Delma Nataly Castelblanco-Martínez; Lorena M. Rios Mendoza; Oscar Frausto-Martínez; Maria del Pilar Blanco-Parra (Science of The Total Environment, 2025)

New paleoecological insights for the Late Pleistocene Neanderthal mountain occurrence at Buena Pinta Cave (Iberian Central System, Pinilla-del-Valle, Madrid, Spain) - Hugues-Alexandre Blain; César Laplana; Christian Sánchez-Bandera; Clara Mielgo; Ángel Blanco-Lapaz; Rafael Marquina-Blasco; Ana Fagoaga; Josep Francesc Bisbal-Chinesta; David Manuel Martín-Perea; Christophe Falguères; Tom Higham; Maria Blanca Ruiz Zapata; et al. (Quaternary Science Reviews, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Integrated Approach to Ship Electrification Using Fuel Cells and an Ammonia Decomposition System - Onur Yuksel; Eduardo Blanco-Davis; David Hitchmough; G Viknash Shagar; Andrew Spiteri; Maria Carmela Di Piazza; Marcello Pucci; Nikolaos Tsoulakos; Milad Armin; Jin Wang (Journal of Marine Science and Engineering, 2025)
This study investigates the environmental and economic performance of integrating a proton exchange membrane fuel cell, battery systems, and an organic Rankine cycle-based waste heat recovery system for ship electrification. The analysis examines an onboard ammonia decomposition system for hydrogen production and ammonia production pathways. Additionally, the study benchmarks the effectiveness of onboard ammonia decomposition against green hydrogen bunkering scenarios (H2-BS). The analysis is based on data collected over two years from a bulk carrier provided by Laskaridis Shipping Co., Ltd. The environmental analysis includes well-to-wake emissions calculations. At the same time, economic performance is assessed through levelised cost of energy (LCOE) computations for 2025 and 2040, factoring in different fuel and carbon price scenarios. Consequently, the analysis utilises the Complex Proportional Assessment method to compare configurations featuring various ammonia production pathways across economic cases. The results indicate that green and pink ammonia feedstocks achieve maximum equivalent carbon dioxide reductions in the electrification plant of up to 47.28% and 48.47%, respectively, compared to H2-BS and 95.56% and 95.66% compared to the base scenario. Ammonia decomposition systems prove more economically viable than H2-BS due to lower storage and fuel costs, leading to competitive LCOE values that improve under higher carbon pricing scenarios.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Therapeutic potential of pranlukast against cuprizone-induced inflammatory demyelination and sensory impairment in mice: Comparison with fingolimod - Greice Nascimento Pires; Renata Pereira Laurindo; Luiza Dos Santos Heringer; Stefanny Calixto da Silva; Débora Magalhães Portela; Ricardo Cardoso; Ana Carolina de Pádua; Ana Beatriz Miranda De Sá; Saulo Augusto Alves Da Cruz; Sheila Espírito Santo Araújo; Ana Maria Blanco Martinez; Milena Batista Carneiro; et al. (NeuroToxicology, 2025)

Species-specific patterns of population genetic structure differ on a microgeographic scale - Sibelle E. O’Donnell; Maria Ruggeri; Macarena Blanco-Pimentel; Megan K. Morikawa; Erika Harms; Johanna Calle-Triviño; Ben A. Flanagan; Harold K. Carlson; Carly D. Kenkel; Wyatt C. Million (Coral Reefs, 2025)
Coral exhibits substantial variation in pelagic larval duration, dispersal range, and population connectivity. In this study, we used reduced representation genotyping to compare the genetic structure of Caribbean reef-building species along the southeastern Dominican Republic coastline to assess connectivity within the likely dispersal kernel. Despite relatively small geographic distance between reefs, species-specific differences in genetic structure were observed. The broadcasting coral Orbicella faveolata had high levels of genetic connectivity. Between the two brooding species, Agaricia agaricites showed strong genetic subdivision, while Porites astreoides exhibited high levels of gene flow . These results suggest that multiple factors outside of life history characteristics influence genetic differentiation among populations, with species-level variability underscoring the importance of restoration and management strategies tailored to individual species, considering regional genetic and environmental variability.

Metabolic profiling of pea (Pisum sativum) cultivars in changing environments: Implications for nutritional quality in animal feed - Pierluigi Reveglia; Mireia Blanco; Maria Josè Cobos; Maryke Labuschagne; Margalida Joy; Diego Rubiales (Food Chemistry, 2025)

Evolutionary derivation inferences of the intrinsic shoulder and brachial muscles in crab-eating raccoon (Procyon cancrivorus, Caniformia, Carnivora) based on the topology, innervation, and anatomical variants - Juan Fernando Vélez García; Diego Alejandro Carrión Blanco; Gabriela Moreno Gómez; Roseâmely Angélica de Carvalho Barros; Maria Angelica Miglino (Zoomorphology, 2024)
The crab-eating raccoon ( Procyon cancrivorus ) is a carnivoran of the family Procyonidae geographically distributed in Central and South America. It is a scansorial species with more terrestrial than arboreal abilities. Previous studies have described the intrinsic shoulder and brachial muscles in this species; however, the terminology and some muscle attachments differ among them. Besides, these studies did not consider the innervation to infer the evolutionary derivation of the muscles, and did not address the arterial supply. The present study aimed to analyze the anatomical arrangement of the intrinsic shoulder and brachial muscles in six Procyon cancrivorus specimens fixed with 10% formaldehyde. The shape, origin, insertion, arterial supply, and variations were described. Furthermore, the innervation previously reported was reviewed again in detail to infer the evolutionary derivation of these muscles. Differences were found with previously reported findings in the same species and other procyonids. Some intraspecific anatomical variants were discovered, such as an accessory head in the biceps brachii muscle bilaterally; a biceps brachii muscle joined to the brachialis muscle unilaterally; and a fusion of the lateral and accessory heads of the triceps brachii muscle. Tensor fasciae antebrachii muscle is divided into two parts in most cases, which are innervated by the radial nerve. The anconeus medialis muscle is independent of the triceps brachii muscle and is innervated by the ulnar nerve. In conclusion, these muscles in P. cancrivorus potentially conserve the evolutionary derivation of the last common ancestor of mammals based on the topology, anatomical variations, and innervation.

Cyclosporin A-loaded dissolving microneedles for dermatitis therapy: Development, characterisation and efficacy in a delayed-type hypersensitivity in vivo model - Miquel Martínez-Navarrete; Antonio José Guillot; Maria C. Lobita; María Carmen Recio; Rosa Giner; Juan Aparicio-Blanco; María Carmen Montesinos; Hélder A. Santos; Ana Melero (Drug Delivery and Translational Research, 2024)
Several drugs can be used for treating inflammatory skin pathologies like dermatitis and psoriasis. However, for the management of chronic and long-term cases, topical administration is preferred over oral delivery since it prevents certain issues due to systemic side effects from occurring. Cyclosporin A (CsA) has been used for this purpose; however, its high molecular weight (1202 Da) restricts the diffusion through the skin structure. Here, we developed a nano-in-micro device combining lipid vesicles (LVs) and dissolving microneedle array patches (DMAPs) for targeted skin delivery. CsA-LVs allowed the effective incorporation of CsA in the hydrophilic DMAP matrix despite the hydrophobicity of the drug. Polymeric matrix composed of poly (vinyl alcohol) (5% w/v), poly (vinyl pyrrolidine) (15% w/v) and CsA-LV dispersion (10% v/v) led to the formation of CsA-LVs@DMAPs with adequate mechanical properties to penetrate the stratum corneum barrier. The safety and biocompatibility were ensured in an in vitro viability test using HaCaT keratinocytes and L929 fibroblast cell lines. Ex vivo permeability studies in a Franz-diffusion cell setup showed effective drug retention in the skin structure. Finally, CsA-LVs@DMAPs were challenged in an in vivo murine model of delayed-type hypersensitivity to corroborate their potential to ameliorate skin inflammatory conditions. Different findings like photon emission reduction in bioluminescence study, normalisation of histological damage and decrease of inflammatory cytokines point out the effectivity of CsA-LVs@DMAPs to treat these conditions. Overall, our study demonstrates that CsA-LVs@DMAPs can downregulate the skin inflammatory environment which paves the way for their clinical translation and their use as an alternative to corticosteroid-based therapies. Graphical Abstract

Carbonaceous fraction in PM2.5 of six Latin American cities: Seasonal variations, sources and secondary organic carbon contribution - Laura Dawidowski; Julián Gelman Constantin; Jorge Herrera Murillo; Miriam Gómez-Marín; Thiago Nogueira; Salvador Blanco Jiménez; Valeria Díaz-Suárez; Facundo Baraldo Victorica; Pablo Lichtig; Melisa Díaz Resquin; Minor Vargas-Rojas; Julio Murillo-Hernández; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Assessing the effects of salinity on microbial communities and pollutant removal in urban wastewater treatment plants - Alvaro Javier Moyano Salcedo; Miguel Cañedo-Argüelles; Sujay S. Kaushal; Eva Maria Ciriero-Cebrián; Adrià Perez-Blanco; Humbert Salvadó (Journal of Water Process Engineering, 2024)

A case study on pharmaceutical residues and antimicrobial resistance genes in Costa Rican rivers: A possible route of contamination for feline and other species - Seiling Vargas-Villalobos; Félix Hernández; David Fabregat-Safont; Denis Salas-González; Francisco Quesada-Alvarado; Ana Maria Botero-Coy; Fernando Esperón; Bárbara Martín-Maldonado; Juan Monrós-Gonzalez; Clemens Ruepert; Sandra Estrada-König; Josué Rivera-Castillo; et al. (Environmental Research, 2024)

Crustal structure of the Western Azuero Peninsula, Panama: Insights into the structure of accretionary complexes and forearc ophiolites - Carolina Ortiz-Guerrero; Camilo Montes; David W. Farris; Catalina Agudelo; Margarita Ariza Acero; Juliana Ayala; Jose David Avellaneda; Alejandro Cortes-Calderon; Esteban Gaitan; Sebastian Garzon; Daniel Gongora-Blanco; Nubia Andrea Jara; et al. (International Geology Review, 2024)

Evaluating the extent and impact of the extreme Storm Gloria on Posidonia oceanica seagrass meadows - Candela Marco-Méndez; Núria Marbà; Ángel Amores; Javier Romero; Mario Minguito-Frutos; María García; Jordi F. Pagès; Patricia Prado; Jordi Boada; José Luis Sánchez-Lizaso; Juan Manuel Ruiz; Gregori Muñoz-Ramos; et al. (Science of The Total Environment, 2024)

Larval performance, osteological development and skeletal abnormalities in wreckfish (Polyprion americanus) under a standard rearing protocol and different light intensities and rearing temperatures - Amin Mokhles Abadi Farahani; Maximo Coronado; Santiago Bragado; Maria José Justo; Xoana Blanco; Aitor Sotelo; Paola Navarrete; Blanca Álvarez-Blázquez; Ignacio Fernández (Aquaculture, 2023)

Environmental exposure to chlorpyrifos during gestation, APOE polymorphism and the risk on autistic-like behaviors - Judit Biosca-Brull; Pia Basaure; Laia Guardia-Escote; Maria Cabré; Jordi Blanco; Miguel Morales-Navas; Fernando Sánchez-Santed; Maria Teresa Colomina (Environmental Research, 2023)

The influence of environmental particulate matter exposure during late gestation and early life on the risk of neurodevelopmental disorders: A systematic review of experimental evidences - Rocío Rodulfo-Cárdenas; Diego Ruiz-Sobremazas; Judit Biosca-Brull; Maria Cabré; Jordi Blanco; Caridad López-Granero; Fernando Sánchez-Santed; Maria Teresa Colomina (Environmental Research, 2023)

European river typologies fail to capture diatom, fish, and macrophyte community composition - Jonathan F. Jupke; Sebastian Birk; Apostolos Apostolou; Jukka Aroviita; Annette Baattrup-Pedersen; Peter Baláži; Libuše Barešová; Saúl Blanco; María Borrego-Ramos; Herman van Dam; Elias Dimitriou; Christian K. Feld; et al. (Science of The Total Environment, 2023)

Biodigestion of easily-acidifying cheese whey in a sequential fermentative-methanogenic process: Strategies for boosting energy production and minimizing alkalinization costs - Vivian Maria Carminato Blanco; Lucas Tadeu Fuess; Matheus Neves Araujo; Marcelo Zaiat (Journal of Water Process Engineering, 2023)

Pathogenicity of Phytophthora and Halophytophthora species on black alder and the host histological response - Cristina Vieites-Blanco; Michele Colangelo; J. Julio Camarero; Maria Caballol; Francisco José García Breijo; Dora Štraus; Jonàs Oliva (Mycological Progress, 2023)
Riparian alder forests are threatened by Phytophthora across Europe. Comparative studies of the pathogenicity of Phytophthora species are crucial for developing effective management strategies. Although only a limited number of species, particularly P. × alni , lead to tree decline in natural environments, many species demonstrate pathogenicity in inoculation trials. Phytophthora species vary in their ability to infect different tissues, such as phloem and xylem, and trigger defence responses in the host through the formation of tyloses and callose. By comparing the histological responses of alder to various Phytophthora species, we can gain insights into the success of P. × alni and the potential damage that could be caused by other species. To investigate the defence strategies of black alder ( Alnus glutinosa ) against attack by Phytophthora and Halophytophthora species present in Catalonia (NE Spain), we conducted inoculation trials on saplings using nine potentially pathogenic species and compared the histological responses. Phytophthora × alni and P. plurivora were the most aggressive species followed by other exotic species such as P. × cambivora and P. cactorum . Phytophthora × alni and P. plurivora were equally damaging despite the higher prevalence of P. × alni in declining alders in natural settings. Although P. × alni mainly invaded the phloem, P. plurivora also invaded the xylem and triggered the production of tyloses. Histological analyses revealed a diverse range of plant responses to infection by Phytophthora species, providing a better understanding of their adaptability in natural environments compared with solely observing lesions. The low level of callose production in saplings inoculated with P. × alni compared with callose production in saplings inoculated with less pathogenic species suggests that P. × alni can evade recognition by the host and, hence, could partially explain its success.

In field study on immune-genes expression during a lactococcosis outbreak in rainbow trout (Oncorhynchus mykiss) - Sarker Mohammed Ibrahim Khalil; Elena Saccà; Marco Galeotti; Simona Sciuto; Nadia Stoppani; Pier Luigi Acutis; Rafet Cagri Öztürk; Konstantina Bitchava; Maria Del Mar Blanco; Lucio Fariano; Marino Prearo; Silvia Colussi; et al. (Aquaculture, 2023)

Vascular allografts for clinical application in Europe: assessment of 30 years of experience with vascular tissue banking in Brussels - Ramadan Jashari; Vanessa Bouzet; Maria-Josee Alcaraz Blanco; Alison Oleffe; Emilie Lecocq; Stefano Mastrobuoni (Cell and Tissue Banking, 2023)

Developmental brain lipidomics is influenced by postnatal chlorpyrifos exposure and APOE genetic background in mice - Laia Guardia-Escote; Judit Biosca-Brull; Maria Cabré; Jordi Blanco; Mikaela Mladenova-Koleva; Pia Basaure; Cristian Pérez-Fernández; Fernando Sánchez-Santed; José L. Domingo; Maria Teresa Colomina (Archives of Toxicology, 2023)
Lipids are a major component of the brain, and are involved in structural and neurodevelopmental processes such as neurogenesis, synaptogenesis and signaling. Apolipoprotein E (apoE) is the main lipoprotein involved in lipid transport in the brain. The apoE isoforms can determine vulnerability to the toxic effects of the pesticide chlorpyrifos (CPF), which can interfere with normal neurodevelopment. We aimed to study the effects of postnatal exposure to CPF and of the APOE genotype on the lipid composition of the brain at early ages. For it, we used apoE3 and apoE4 targeted-replacement (TR) male mice, as well as wild-type C57BL/6. The mice were orally exposed to 1 mg/kg/day of CPF on postnatal days 10–15 and, four hours after the treatment, we obtained samples to assess the cerebral lipid composition. Differences between APOE genotypes were found in the cerebral lipid profile in the postnatal period. ApoE4-TR mice exhibited higher lipid concentrations compared to the other groups in most of the cases. CPF exposure led to a decrease in cholesteryl ester and triglyceride concentrations, while modulating the levels of phosphatidylcholine species based on the apoE isoform. Specifically, CPF treatment decreased the concentration of some species of this lipid (PC30:0, PC31:0, PC32:2, PC36:5, PC40:4 and PC40:5) in C57BL/6 mice exposed to CPF, increased (PC31:0 and PC37:6) in apoE3-TR exposed mice while exposed apoE4-TR mice remained unaltered. These results provide further insights into the lipid composition of the brain at early ages, and how it can be modulated by environmental and genetic factors.

Introducing GoNEXUS SEF: a solutions evaluation framework for the joint governance of water, energy, and food resources - Adrián González-Rosell; Imen Arfa; Maria Blanco (Sustainability Science, 2023)
To enhance water, energy, and food security and promote ecosystems conservation, it is necessary to design policies or solutions capable of addressing cross-sectoral challenges. In this paper, GoNEXUS SEF, an evaluation framework for co-designing and evaluating nexus solutions, is presented. This framework provides guidelines for conducting a nexus-coherence assessment to improve the governance of the water-energy-food-ecosystems nexus. The assessment involves a participatory process that integrates qualitative and quantitative methodologies through systemic approaches. The crucial aspects necessary in the development of methodologies that address the nexus have been identified and considered. The framework was applied to a practical case study, an increase in the irrigation water price in Andalusia—Spain for the horizon of 2030. Case study results revealed that the measure can generate synergies since it favours water savings, irrigation water efficiency and ecosystems conservation. However, trade-offs are observed, mainly undermining the economic development of agriculture in the region. GoNEXUS SEF has proven capable of evaluating nexus solutions by measuring cross-sectoral synergies and trade-offs. It highlights hidden properties and identifies leverage points and key aspects of a complex cross-sectoral system to apply nexus solutions more effectively to promote sustainable development. In addition, the framework can be adapted to fit different case studies, considering their own challenges and their spatial and temporal scales, which gives it a competitive advantage over other methodologies focused on analysing the nexus. Graphical abstarct

The effects of exposure to road traffic noise at school on central auditory pathway functional connectivity - Gerard Martínez-Vilavella; Jesus Pujol; Laura Blanco-Hinojo; Joan Deus; Ioar Rivas; Cecilia Persavento; Jordi Sunyer; Maria Foraster (Environmental Research, 2023)

Detection and analysis of Shiga toxin producing and enteropathogenic Escherichia coli in cattle from Tierra del Fuego, Argentina - Maria Paz Bonino; Ximena Blanco Crivelli; Juan Facundo Petrina; Sebastian Galateo; Tania Aparecida Tardelli Gomes; Armando Navarro; Cecilia Cundon; Alicia Broglio; Mariana Sanin; Adriana Bentancor (Brazilian Journal of Microbiology, 2023)

Impact of gilt immunocastration on weight losses and instrumental and chemical characteristics of Teruel dry-cured ham - Leticia Pérez-Ciria; Guillermo Ripoll; María Á. Sanz; Mireia Blanco; Francisco J. Miana-Mena; Maria A. Latorre (Meat Science, 2023)

Exposure to chlorpyrifos during pregnancy differentially affects social behavior and GABA signaling elements in an APOE- and sex-dependent manner in a transgenic mouse model - Judit Biosca-Brull; Laia Guardia-Escote; Pia Basaure; Maria Cabré; Jordi Blanco; Cristian Pérez-Fernández; Fernando Sánchez-Santed; José L. Domingo; Maria Teresa Colomina (Environmental Research, 2023)

Pigmented cereals and legume grains as healthier alternatives for brewing beers - Giuseppe Romano; Maria Tufariello; Nadia Calabriso; Laura Del Coco; Francesco P. Fanizzi; Antonio Blanco; Maria A. Carluccio; Francesco Grieco; Barbara Laddomada (Food Bioscience, 2023)

Model of transferability for the rainfall erosivity factor - Ana Júlia Soares da Silva Barbosa; Claudio José Cavalcante Blanco; Adayana Maria Queiroz de Melo; Carlos Eduardo Aguiar de Souza Costa; Patrícia da Silva Holanda (Sustainable Water Resources Management, 2023)

Toxic plants from the perspective of a “Quilombola” community in the Cerrado region of Brazil - Ricardo de Castro Santos Paim; Luiza Gabriella Ferreira de Paula; Débora Moreira Soares; Tarik Fernandes Gonçalves Rocha; Amanda Lopes Ribeiro; Natália Barros; Fabrício Carrião dos Santos; Heleno Dias Ferreira; Vera Lúcia Gomes-Klein; Benito Soto-Blanco; José Paes de Oliveira-Filho; Paulo Henrique Jorge da Cunha; et al. (Toxicon, 2023)

Transcriptional profiling of the terpenoid biosynthesis pathway and in vitro tests reveal putative roles of linalool and farnesal in nectarine resistance against brown rot - Marta Balsells-Llauradó; Núria Vall-llaura; Josep Usall; Christian J. Silva; Barbara Blanco-Ulate; Neus Teixidó; Maria Caballol; Rosario Torres (Plant Science, 2023)

Spatio-temporal distribution of particulate matter and wood-smoke tracers in Temuco, Chile: A city heavily impacted by residential wood-burning - Maria Elisa Quinteros; Estela Blanco; Janeet Sanabria; Felipe Rosas-Diaz; Carola A. Blazquez; Salvador Ayala; Juan Pablo Cárdenas-R; Elizabeth A. Stone; Keely Sybesma; Juana Maria Delgado-Saborit; Roy M. Harrison; Pablo Ruiz-Rudolph (Atmospheric Environment, 2023)

Influence of landscape ecology and physiological implications in bats from different trophic guilds - Camila Guimarães Torquetti; Thaynara Parente de Carvalho; Renata Maria Pereira de Freitas; Mariella Bontempo Freitas; Ana Tereza Bittencourt Guimarães; Benito Soto-Blanco (Science of The Total Environment, 2023)

A new Trophic Diatom Index for Tropical Reservoirs (TDIR) - Angela Maria da Silva-Lehmkuhl; Saúl Blanco; Denise C. Bicudo (Hydrobiologia, 2022)

Elaborating rating curves for implementation of the MGB hydrological model in a river basin, Amazon region, Brazil - Adayana Maria Queiroz de Melo; Claudio José Cavalcante Blanco; Paulo Rógenes Monteiro Pontes; Rosane Barbosa Lopes Cavalcante; Renato Oliveira da Silva-Júnior; Marcio Sousa da Silva (Sustainable Water Resources Management, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

A relict oasis of living deep-sea mussels Bathymodiolus and microbial-mediated seep carbonates at newly-discovered active cold seeps in the Gulf of Cádiz, NE Atlantic Ocean - Luis Somoza; José Luis Rueda; Francisco J. González; Blanca Rincón-Tomás; Teresa Medialdea; Olga Sánchez-Guillamón; Michael Hoppert; Juan T. Vázquez; Pedro Madureira; Esther Santofimia; Enrique López-Pamo; Desirée Palomino; et al. (PalZ, 2021)
Extensive beds of the deep-sea mussel Bathymodiolus mauritanicus (currently also known as Gigantidas mauritanicus ) linked to active cold seeps related to fissure-like activity on Al Gacel mud volcano, Gulf of Cádiz, were filmed and sampled for the first time during the oceanographic expedition SUBVENT-2 aboard R/V Sarmiento de Gamboa. Al Gacel mud volcano is one of up to 80 fluid venting submarine structures (mud volcanoes and mud volcano/diapir complexes) identified in the Gulf of Cádiz as result of explosive venting of hydrocarbon-enriched fluids sourced from deep seated reservoirs. This mud volcano is a cone-shaped edifice, 107 m high, 944 m in diameter constituted by mud breccias and, partially covered by pavements of seep carbonates. Extensive beds of this deep-sea mussel were detected at the northern flank at 810–815 m water depth associated with bacterial mats around intermittent buoyant vertical bubble methane plumes. High methane concentrations were measured in the water column above living mussel beds. Other chemosymbiotic species ( Siboglinum sp., Solemya elarraichensis , Isorropodon sp., Thyasira vulcolutre and Lucinoma asapheus ) were also found in different parts of Al Gacel mud volcano. Al Gacel mud volcano may currently represent one of the most active mud volcanoes in the Gulf of Cádiz, delivering significant amounts of thermogenic hydrocarbon fluids which contribute to foster the extensive chemosynthesis-based communities detected. This finding is of paramount importance for linking extremophile bivalve populations along the North Atlantic, including cold seeps of the Gulf of México, hydrothermal vents of the Mid-Atlantic Ridge and now, detailed documented at the Gulf of Cádiz.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Mitochondrial DNA genome evidence for the existence of a third divergent lineage in the western Atlantic Ocean for the bull shark ( Carcharhinus leucas ) - Nadia Sandoval Laurrabaquio‐Alvarado; Píndaro Díaz‐Jaimes; Silvia Hinojosa‐Álvarez; Maria del Pilar Blanco‐Parra; Douglas H. Adams; Juan Carlos Pérez‐Jiménez; J. Leonardo Castillo‐Géniz (Journal of Fish Biology, 2021)
We report for the first time a highly divergent lineage in the Caribbean Sea for the bull shark ( Carcharhinus leucas ) based on the analysis of 51 mitochondrial DNA genomes of individuals collected in the western North Atlantic. When comparing the mtDNA control region obtained from the mitogenomes to sequences reported previously for Brazil, the Caribbean lineage remained highly divergent. These results support the existence of a discrete population in Central America due to a phylogeographic break separating the Caribbean Sea from the western North Atlantic, Gulf of Mexico and South America.

Comparison of various serological assays for novel SARS-COV-2 - María Simón Sacristan; Ana Collazos-Blanco; Maria Isabel Zamora Cintas; Alicia Serrano García; Carmen Ybarra de Villavicencio; María Mateo Maestre (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

SPION and doxorubicin-loaded polymeric nanocarriers for glioblastoma theranostics - Edurne Luque-Michel; Laurent Lemaire; Maria J. Blanco-Prieto (Drug Delivery and Translational Research, 2021)

Malva sylvestris derivatives as inhibitors of HIV-1 BaL infection - Bruna Benso; Pedro Luiz Rosalen; Silvana Pasetto; Maria Carolina Salomé Marquezin; Verônica Freitas–Blanco; Ramiro Mendonça Murata (Natural Product Research, 2021)

Protein Kinase C-Gamma Knockout Mice Show Impaired Hippocampal Short-Term Memory While Preserved Long-Term Memory - Maria Gomis-González; Lorena Galera-López; Marc Ten-Blanco; Arnau Busquets-Garcia; Thomas Cox; Rafael Maldonado; Andrés Ozaita (Molecular Neurobiology, 2021)

Influence of the constructive features of RC existing buildings in their ductility and seismic performance - Maria-Victoria Requena-Garcia-Cruz; Antonio Morales-Esteban; Percy Durand-Neyra; Beatriz Zapico-Blanco (Bulletin of Earthquake Engineering, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Developing a multi-attribute decision aid model for selection of a weather radar supplier - Amaury Caruzzo; Cintia Maria Rodrigues Blanco; Paul Joe (Environment Systems and Decisions, 2020)

Performance enhancement and sample throughput increase of a multiresidue pesticides method in fruits and vegetables using Data-Dependent MS acquisition - David Tonoli; Aline Staub Spörri; Maria Blanco; Philippe Jan; Jean-Paul Larcinese; Patricia Schmidt-Millasson; Didier Ortelli; Patrick Edder (Food Additives & Contaminants: Part A, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Study of the strength of the evidence and the redundancy of the research on pharmacological treatment for Alzheimer’s disease: a cumulative meta-analysis and trial sequential analysis - Lídia Blanco-Silvente; Xavier Castells; Josep Garre-Olmo; Joan Vilalta-Franch; Marc Saez; Maria Antònia Barceló; Dolors Capellà (European Journal of Clinical Pharmacology, 2019)

An Online Survey of Occupational Hazards in Brazilian Aquaculture - Flavielle Blanco Marques; Giovani Nícolas Bettoni; Benito de Brito; Kelly Cristina Tagliari de Brito; Maria Helena Fermino; Dorothy Ngajilo; Augusto Sávio Peixoto Ramos; Bruno Gomes Tavares dos Santos; Marcia Regina Stech; Andrew Watterson; Lissandra Souto Cavalli (Journal of Agromedicine, 2019)

2015 Beers Criteria and STOPP v2 for detecting potentially inappropriate medication in community-dwelling older people: prevalence, profile, and risk factors - Encarnación Blanco-Reina; Jenifer Valdellós; Lorena Aguilar-Cano; Maria Rosa García-Merino; Ricardo Ocaña-Riola; Gabriel Ariza-Zafra; Inmaculada Bellido-Estévez (European Journal of Clinical Pharmacology, 2019)

Pharmacological modulation of the behavioral effects of social defeat in memory and learning in male mice - M Carmen Blanco-Gandia; Sandra Montagud-Romero; Javier Navarro-Zaragoza; Elena Martínez-Laorden; Pilar Almela; Cristina Nuñez; Maria-Victoria Milanés; María-Luisa Laorden; José Miñarro; Marta Rodríguez-Arias (Psychopharmacology, 2019)

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Implications of climate change for semi-arid dualistic agriculture: a case study in Central Chile - Francisco J. Fernández; Maria Blanco; Roberto D. Ponce; Felipe Vásquez-Lavín; Lisandro Roco (Regional Environmental Change, 2019)

Correction to: the relative importance of subjective and structural factors for individual adaptation to climate change by forest owners in Sweden - Gregor Vulturius; Karin André; Åsa Gerger Swartling; Calum Brown; Mark D. A. Rounsevell; Anna Maria Jönsson; Victor Blanco (Regional Environmental Change, 2018)

New mechanistic insights on the metabolic-disruptor role of chlorpyrifos in apoE mice: a focus on insulin- and leptin-signalling pathways - Fiona Peris-Sampedro; Jordi Blanco; Maria Cabré; Pia Basaure; Laia Guardia-Escote; Jose L. Domingo; Domènec J. Sánchez; Maria Teresa Colomina (Archives of Toxicology, 2018)

Changes in gene expression and sensitivity of cocaine reward produced by a continuous fat diet - M. Carmen Blanco-Gandía; Auxiliadora Aracil-Fernández; Sandra Montagud-Romero; Maria A. Aguilar; Jorge Manzanares; José Miñarro; Marta Rodríguez-Arias (Psychopharmacology, 2017)

Repeated social defeat and the rewarding effects of cocaine in adult and adolescent mice: dopamine transcription factors, proBDNF signaling pathways, and the TrkB receptor in the mesolimbic system - Sandra Montagud-Romero; Cristina Nuñez; M Carmen Blanco-Gandia; Elena Martínez-Laorden; María A Aguilar; Javier Navarro-Zaragoza; Pilar Almela; Maria-Victoria Milanés; María-Luisa Laorden; José Miñarro; Marta Rodríguez-Arias (Psychopharmacology, 2017)

Genetic diversity and structure of Brazilian ginger germplasm (Zingiber officinale) revealed by AFLP markers - Eleonora Zambrano Blanco; Miklos Maximiliano Bajay; Marcos Vinícius Bohrer Monteiro Siqueira; Maria Imaculada Zucchi; José Baldin Pinheiro (Genetica, 2016)

Quality assurance of diatom counts in Europe: towards harmonized datasets - Maria Kahlert; Éva Ács; Salome F. P. Almeida; Saúl Blanco; Mirko Dreßler; Luc Ector; Satu Maaria Karjalainen; Antonia Liess; Adrienne Mertens; Jako van der Wal; Sirje Vilbaste; Petra Werner (Hydrobiologia, 2016)

Water Variability and the Economic Impacts on Small-Scale Farmers. A Farm Risk-Based Integrated Modelling Approach - Francisco J. Fernández; Roberto D. Ponce; Maria Blanco; Diego Rivera; Felipe Vásquez (Water Resources Management, 2016)

Cyclic AMP deficiency negatively affects cell growth and enhances stress-related responses in tobacco Bright Yellow-2 cells - Wilma Sabetta; Candida Vannini; Alessandra Sgobba; Milena Marsoni; Annalisa Paradiso; Francesca Ortolani; Marcella Bracale; Luigi Viggiano; Emanuela Blanco; Maria Concetta de Pinto (Plant Molecular Biology, 2016)

Temperature and fish community in the Cantabrian Sea - Punzon Merino Antonio; Lopez Lopez Lucia; González Irusta Jose Manuel; Preciado Ramirez Izaskun; Hidalgo Manuel; Serrrano Alberto; Tel Elena; Ruiz Susana; Fernandez Zapico Olaya; Blanco Giner Maria Angeles (Frontiers in Marine Science, 2016)

Optimal design of cogeneration system based on exergoenvironmental analysis - Pooya Navid; Mohammad Hasan Khoshgoftar Manesh; Ana Maria Blanco Marigorta (Clean Technologies and Environmental Policy, 2014)

Reduced seed predation after invasion supports enemy release in a broad biogeographical survey - Eva Castells; Maria Morante; José M. Blanco-Moreno; F. Xavier Sans; Roser Vilatersana; Anabel Blasco-Moreno (Oecologia, 2013)

Prevalence of asthma symptoms in schoolchildren, and climate in west European countries: an ecologic study - Alberto Arnedo-Pena; Luis García-Marcos; Alberto Bercedo-Sanz; Inés Aguinaga-Ontoso; Carlos González-Díaz; Águeda García-Merino; Rosa Busquets-Monge; Maria Morales Suárez-Varela; Juan Batlles-Garrido; Alfredo A. Blanco-Quirós; Angel López-Silvarrey; Gloria García-Hernández; et al. (International Journal of Biometeorology, 2013)

Muscle development and body growth in larvae and early post-larvae of shi drum, Umbrina cirrosa L., reared under different larval photoperiod: muscle structural and ultrastructural study - Maria D. Ayala; Emilia Abellán; Marta Arizcun; Alicia García-Alcázar; F. Navarro; Alfonso Blanco; Octavio M. López-Albors (Fish Physiology and Biochemistry, 2013)

Application of Fenton, photo-Fenton, solar photo-Fenton, and UV/H2O2 to degradation of the antineoplastic agent mitoxantrone and toxicological evaluation - Rodrigo Pereira Cavalcante; Lucas da Rocha Sandim; Danielle Bogo; Antônio Marcos Jacques Barbosa; Marly Eiko Osugi; Matildes Blanco; Silvio Cesar de Oliveira; Maria de Fatima Cepa Matos; Amilcar Machulek; Valdir Souza Ferreira (Environmental Science and Pollution Research, 2013)

A high-density consensus map of A and B wheat genomes - Daniela Marone; Giovanni Laidò; Agata Gadaleta; Pasqualina Colasuonno; Donatella B. M. Ficco; Angelica Giancaspro; Stefania Giove; Giosué Panio; Maria A. Russo; Pasquale De Vita; Luigi Cattivelli; Roberto Papa; et al. (Theoretical and Applied Genetics, 2012)

Ecological assessment of Portuguese reservoirs based on littoral epilithic diatoms - Maria Helena Novais; Saúl Blanco; Cristina Delgado; Manuela Morais; Lucien Hoffmann; Luc Ector (Hydrobiologia, 2012)

Identification versus counting protocols as sources of uncertainty in diatom-based ecological status assessments - Maria Kahlert; Martyn Kelly; Raino-Lars Albert; Salomé F. P. Almeida; Tomáš Bešta; Saúl Blanco; Michel Coste; Luc Denys; Luc Ector; Markéta Fránková; Daša Hlúbiková; Plamen Ivanov; et al. (Hydrobiologia, 2012)

A novel hybrid promoter responsive to pathophysiological and pharmacological regulation - Maria C. Subang; Rewas Fatah; Carly Bright; Patricia Blanco; Mariana Berenstein; Ying Wu; Osvaldo L. Podhajcer; Paul G. Winyard; Yuti Chernajovsky; David Gould (Journal of Molecular Medicine, 2012)

Taxonomic and phylogenetic revision of three rare irpicoid species within the Meruliaceae - Gabriel Moreno; Maria-Natividad Blanco; Julia Checa; Gonzalo Platas; Fernando Peláez (Mycological Progress, 2011)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Sunny hours and variations in the prevalence of asthma in schoolchildren according to the International Study of Asthma and Allergies (ISAAC) Phase III in Spain - Alberto Arnedo-Pena; Luis García-Marcos; Jorge Fuertes Fernández-Espinar; Alberto Bercedo-Sanz; Ines Aguinaga-Ontoso; Carlos González-Díaz; Ignacio Carvajal-Urueña; Rosa Busquet-Monge; Maria Morales Suárez-Varela; Nagore García de Andoin; Juan Batlles-Garrido; Alfredo Blanco-Quirós; et al. (International Journal of Biometeorology, 2011)

A Generic Bio-Economic Farm Model for Environmental and Economic Assessment of Agricultural Systems - Sander Janssen; Kamel Louhichi; Argyris Kanellopoulos; Peter Zander; Guillermo Flichman; Huib Hengsdijk; Eelco Meuter; Erling Andersen; Hatem Belhouchette; Maria Blanco; Nina Borkowski; Thomas Heckelei; et al. (Environmental Management, 2010)

Identity of the cells recruited to a lesion in the central nervous system of a decapod crustacean - Paula Grazielle Chaves-da-Silva; Cintia Monteiro de Barros; Flávia Regina Souza Lima; Adriano Biancalana; Ana Maria Blanco Martinez; Silvana Allodi (Cell and Tissue Research, 2010)

Multiparametric comparison of mesenchymal stromal cells obtained from trabecular bone by using a novel isolation method with those obtained by iliac crest aspiration from the same subjects - Fermin M. Sanchez-Guijo; Juan F. Blanco; Graciela Cruz; Sandra Muntion; Maria Gomez; Soraya Carrancio; Olga Lopez-Villar; Maria-Victoria Barbado; Luis-Ignacio Sanchez-Abarca; Belén Blanco; Jesus G. Briñon; Maria-Consuelo del Cañizo (Cell and Tissue Research, 2009)

Anthraquinones from in vitro root culture of Morinda royoc L. - Janetsy Borroto; Josep Coll; Maribel Rivas; Maria Blanco; Oscar Concepción; Yudelsy A. Tandrón; Martha Hernández; Reinaldo Trujillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Sporothrix schenckii isolated fromdomestic cats with and without sporotrichosis in Rio de Janeiro, Brazil - Tânia Maria Pacheco Schubach; Armando de Oliveira Schubach; Rosani Santos dos Reis; Tullia Cuzzi-Maya; Tânia Cristina Moita Blanco; Dilma Ferreira Monteiro; Mônica Bastos de Lima Barros; Ricardo Brustein; Rosely Maria Zancopé-Oliveira; Paulo Cezar Fialho Monteiro; Bodo Wanke (Mycopathologia, 2002)

Phylogenetic Analysis of Foot-and-Mouth Disease Viruses Isolated in Argentina - Guido König; Carlos Blanco; Nick J. Knowles; Eduardo L. Palma; Eduardo Maradei; Maria Elisa Piccone (Virus Genes, 2001)

Storage proteins in sugarcane: An interesting exception in monocots - Maria A. de los Blanco; Magdalena Segura-Nieto; Ramiro Castillo; Nadina Nieves (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Changes in sleep after acute and repeated administration of nicotine in the rat - Rafael J. Salin-Pascual; Maria Luisa Moro-Lopez; Hector Gonzalez-Sanchez; Carlos Blanco-Centurion (Psychopharmacology, 1999)

Artificial endosperm of Cleopatra tangerine zygotic embryos: a model for somatic embryo encapsulation - Nadina Nieves; Jose C. Lorenzo; Maria de los A. Blanco; Justo González; Hipólito Peralta; Martha Hernández; Ramón Santos; Oscar Concepción; Carlos G. Borroto; Eduviges Borroto; Raúl Tapia; Marcos E. Martinez; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Effect of magnesium sulfate administration on subendocardial and subepicardial perfusion - Panayotis Fantidis; Tom Arne Stiris; Dolores Blanco; Rosario Madero Jarabo; Maria JesÚs Del Cerro; Maria Aurora Fernández Ruiz (Biological Trace Element Research, 1997)

Aerobiological study of fungal spores from Palencia (Spain) - Baudilio Herrero; M. Amor Fombella-Blanco; Delia Fernández-González; Rosa Maria Valencia-Barrera (Aerobiologia, 1996)